Innovation and Capacity Building Cross-disciplinary Management Theories for Practical Applications (Palgrave Studies in Cross-disciplinary Business Research, In Association with EuroMed Academy of Business, 2018)
This book explores how contemporary organisations are abandoning conventional tactics in order to survive and grow in an incessantly shifting business landscape, analysing fundamental aspects of management, marketing and strategy from an interdisciplinary perspective. Focusing on the paradigms of neuro-marketing, innovative change management, motivational creativity, and customer data management, to name a few, the authors provide practical learning outcomes which reflect how organisations are seeking to adopt innovative means to innovative ends, targeting capacity building in multiple ways. Ultimately, this edited collection implicitly defines an organisational philosophy that incorporates functionality, but also embraces business notions pertaining to wider contextual transformations and environmental developments. Theoretical and practical contributions highlight the importance of multidisciplinary research to practical business success, making this book an invaluable read to both scholars and business executives.